Strategi Manajemen Praktik Dokter Hewan Mandiri dalam Melayani Pasien Hewan Besar dan Hewan Kesayangan: Studi Praktek drh. Lailatus Sa’diyah - Eka Aprianto Nur Setiawan; Agung Dwi Nugroho (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to explore the management strategies employed by an independent veterinarian in serving both large animals and companion animals, with a focus on the practice of Dr. Lailatus Sa’diyah in Pasuruan Regency, East Java. This phenomenon is crucial to investigate as independent veterinary practices face dual challenges in addressing the distinct needs of these two animal groups, yet there is limited in-depth research on this topic in the Indonesian context. A qualitative approach with an intrinsic case study design was applied. Data were collected through semi-structured interviews, participant observation, and documentation. The main participant was Dr. Lailatus Sa’diyah, supported by several clients and practice partners selected purposively. The findings reveal three main themes: (1) time management and mobile services to address cross-species and geographical demands, (2) empathetic, educational communication strategies to build client trust, and (3) the role of gender and personal branding in strengthening professional image. These findings contribute to a deeper understanding of independent veterinary practice as a socially embedded entity that adapts to local contexts. The practical implications support the development of field-based training policies and community-based veterinary service models. Future research is recommended to explore similar dynamics across different regions and practice types.